2016
DOI: 10.1007/s00037-016-0141-z
|View full text |Cite
|
Sign up to set email alerts
|

Deterministic Identity Testing for Sum of Read-Once Oblivious Arithmetic Branching Programs

Abstract: A read-once oblivious arithmetic branching program (ROABP) is an arithmetic branching program (ABP) where each variable occurs in at most one layer. We give the first polynomial time whitebox identity test for a polynomial computed by a sum of constantly many ROABPs. We also give a corresponding blackbox algorithm with quasi-polynomial time complexity n O(log n) . In both the cases, our time complexity is double exponential in the number of ROABPs.ROABPs are a generalization of set-multilinear depth-3 circuits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…Our construction of s(t 1 ,t 2 ) comes from the basis isolating weight assignment for ROABPs from Agrawal et al [2]. We use the fact that for any polynomial over a k-dimensional algebra, shift by a basis isolating map achieves log(k + 1)-concentration [17].…”
Section: Rank-concentrationmentioning
confidence: 99%
See 2 more Smart Citations
“…Our construction of s(t 1 ,t 2 ) comes from the basis isolating weight assignment for ROABPs from Agrawal et al [2]. We use the fact that for any polynomial over a k-dimensional algebra, shift by a basis isolating map achieves log(k + 1)-concentration [17].…”
Section: Rank-concentrationmentioning
confidence: 99%
“…Gurjar et al [17,Lemma 5.2] have shown that shifting by a basis isolating weight assignment achieves concentration. We write their lemma here without a proof.…”
Section: Basis Isolationmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, in the boolean domain, pseudorandom generators for read-once branching programs in unknown order are much weaker, in terms of the seed length, than Nisan's generator [Nis92] which works only if the order is known. Recently, Gurjar et al obtained PIT algorithms for sum of ROABPs [GKST15].…”
Section: Introductionmentioning
confidence: 99%
“…Some results were known for the more restricted model of a sum of k ROABPs (e.g. [GKST15]), and we give more details on those in Section 1.3.…”
Section: Introductionmentioning
confidence: 99%